2006
DOI: 10.1016/j.ejpain.2005.11.004
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between activity and pain in patients 6 months after lumbar disc surgery: Do pain‐related coping modes act as moderator variables?

Abstract: The assessment of pain-related coping modes yielded an important differentiation between subgroups of LBP patients 6 months after surgery. Endurance copers displayed signs of overuse in their daily behavior in spite of pain than adaptive copers. The one fear avoidance coper tends to do less physical activity in the sense of underuse.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
2
6

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 46 publications
6
70
2
6
Order By: Relevance
“…17,18 This is not surprising as everyone has a different physical capacity and in a chronic pain population this would not be exclusively determined by avoiding or persisting with activity. While low…”
Section: 11mentioning
confidence: 99%
“…17,18 This is not surprising as everyone has a different physical capacity and in a chronic pain population this would not be exclusively determined by avoiding or persisting with activity. While low…”
Section: 11mentioning
confidence: 99%
“…Undue suppression of normal, pain-related interruption of daily activities may lead to an overuse or overload of musculoskeletal structures, thereby attenuating physical recovery. Preliminary evidence suggests that excessive task persistence might predict less successful rehabilitation (see 89,90 ), and may eventually increase vulnerability for inflammatory diseases 91 . However, more systematic research on the potential effects of long term persistence is needed.…”
Section: Ignoring Pain and Goal Persistencementioning
confidence: 99%
“…For example, one potential mediator could be fear of movement/(re)injury, which has been shown to be a strong predictor of pain-related disability in chronic pain patients (e.g., Vlaeyen et al, 1995); another potential mediator could be an individual's activity patterns (e.g., avoidance, overdoing and pacing), which also play an important role in the development and maintenance of chronic pain (Hasenbring et al, 2006;Nielson, et al, 2001;Philips & Rachman, 1996); a final potential mediator could be pain-related self-efficacy, which has been associated with lower levels of pain intensity, disability, depression and anxiety (e.g., Arnstein, 2000;Costa et al, 20 2011; Nicholas, 2007). Indeed, from a biopsychosocial perspective on chronic pain (e.g., Turk & Gatchel, 2013) the present study only addresses how social and physical variables influence pain disability/severity.…”
Section: Limitations Implications and Directions For Future Researchmentioning
confidence: 99%
“…To date, a large body of research has identified cognitive (e.g., catastrophizing, pain-related self-efficacy), affective (e.g. pain-related fear) and behavioral (e.g., activity dis/engagement) determinants of painrelated disability (e.g., Arnstein, 2000;Costa et al, 2011;Hasenbring et al, 2006;Nicholas, 2007;Nielson, et al, 2001;Philips & Rachman, 1996;Vlaeyen et al, 1995). The extent to which these determinants may act as mediators of the influence of perceived promotion of autonomy and dependence on pain-related disability is yet to be explored.…”
Section: Introductionmentioning
confidence: 99%